La notion de potentiel agronomique en droit de l’urbanisme : une invisibilisation de la qualité des sols par les enjeux socio-spatiaux du foncier agricole - Julie Célia Itey; Adrien Baysse-Lainé; Maylis Desrousseaux (Développement Durable et Territoires)
There are very few legal provisions based on soil characteristics. In France, one of them states that the agricultural zoning of urban planning documents can be attentive to the « agronomic, economic and biological potential » of plots. This article examines the coherence between the interpretation of this criterion by administrative judges and other stakeholders, and the scientific definition of soil quality as its capacity to perform functions. While certain similarities can be observed, it appears that soil quality is invisible when it comes to the socio-spatial issues surrounding farmland.